The Proliferation Of Nuclear Weapons - Ali Muhammad (FISIP 2004 UMY, 2015)
This article examines lhe proliferation of nuclear weapon. ll asks the lollowing questions: why do nalions go nuclear, what is the impact of nuclear proliferation on global security, how !o stop nuclear proliferation, and to what extent is the global nuclear regime successful in preventing nuclear proliferations. lt will be argued that, frrsl, no single factor is able to explain why nation go nuclear. lt is necessary lo consider a range of variables which may have an influence on nuclear proliferation decisions. Secod4 in conuast to pro-proliferation position, it argues that the nuclear proliferalion is very dangerous for the global securiry. fhrb, lhe global nuclear non-proliferation regime, Non-Proliferation Treaty, has achieved mix result. Most states comply with the rule of the regime because they see that their national interests are congruenl with the regime. However, there are negative developmentsr there are states (lsrael) that refuse to join NPT; some other stiates defy the rule ofthe regime. Finally, it goes on to a.gue that intemational conrmunityshould strengthen the NPT regime io make a safe and secure world.